Understanding media semiotics - Danesi, Marcel 1946- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2019)
"Media semiotics is a valuable method of focusing on the hidden meanings within media texts. This new edition brings Understanding Media Semiotics fully up to date and is written for students of the media, of linguistics and those interested in studying the ever-changing media in more detail. Offering an in-depth guide to help students investigate and understand the media using semiotic theory, this book assumes little previous knowledge of semiotics or linguistics, avoiding jargon and explaining the issues step by step. With in-depth case studies, practical accounts and directed further reading, Understanding Media Semiotics provides students with all the tools they need to understand semiotic analysis in the context of the media. Semiotic analysis is sometimes seen as complicated and difficult to understand; Marcel Danesi shows that on the contrary it can be readily understood and can greatly enrich students' understanding of media texts, from print media right through to the internet and apps."--Provided by publisher.